2018
DOI: 10.1038/s41598-018-30810-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the diagnostic accuracy of Computer-Aided Detection of tuberculosis on Chest radiography among private sector patients in Pakistan

Abstract: The introduction of digital CXR with automated computer-aided interpretation, has given impetus to the role of CXR in TB screening, particularly in low resource, high-burden settings. The aim of this study was to evaluate the diagnostic accuracy of CAD4TB as a screening tool, implemented in the private sector in Karachi, Pakistan. This study analyzed retrospective data from CAD4TB and Xpert MTB/RIF testing carried out at two private TB treatment and diagnostic centers in Karachi. Sensitivity, specificity, pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
51
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 32 publications
(40 reference statements)
1
51
1
Order By: Relevance
“…Our study findings indicate that CAD4TB offers good diagnostic accuracy as a triage test for TB screening among PWD using Xpert MTB/RIF as the reference standard. However, in comparison with the CAD4TB evaluation conducted in Pakistan among individuals with an unknown diabetes status that reported sensitivities in the range 91.0-97.3%, our current study shows lower sensitivities (range 48.6-90.5%) for the corresponding CAD4TB cut-offs on the same version of CAD4TB software on the same version of CAD4TB software 5 . A recent study from Indonesia evaluating CAD4TB among PWD reported an AUC of 0.89 using against the reference standard of bacteriologically and clinically confirmed TB (7 bacteriologically confirmed TB cases and 2 clinically diagnosed) 12 .…”
Section: Discussioncontrasting
confidence: 83%
See 3 more Smart Citations
“…Our study findings indicate that CAD4TB offers good diagnostic accuracy as a triage test for TB screening among PWD using Xpert MTB/RIF as the reference standard. However, in comparison with the CAD4TB evaluation conducted in Pakistan among individuals with an unknown diabetes status that reported sensitivities in the range 91.0-97.3%, our current study shows lower sensitivities (range 48.6-90.5%) for the corresponding CAD4TB cut-offs on the same version of CAD4TB software on the same version of CAD4TB software 5 . A recent study from Indonesia evaluating CAD4TB among PWD reported an AUC of 0.89 using against the reference standard of bacteriologically and clinically confirmed TB (7 bacteriologically confirmed TB cases and 2 clinically diagnosed) 12 .…”
Section: Discussioncontrasting
confidence: 83%
“…In addition, the association of glycemic control with CAD4TB scores and MTB positivity was not evaluated in this study. Another limitation of this study is that the symptoms data was not recorded which can be an important factor in risk assessment for CAD scores and enhance the performance of the software 5 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this alone will not obviate the need for visiting health facility, as contacts also have to undergo chest radiography. To address this, we recommend exploring the possibility of using new technologies such as digital chest radiography with automated computer-aided detection of tuberculosis, which can be mounted in a mobile van for greater outreach [24].…”
Section: Discussionmentioning
confidence: 99%